Pengaruh Suasana Toko, Promosi dari Mulut ke Mulut dan Kualitas Pelayanan terhadap Keputusan Menggunakan Jasa pada Suasana Barbershop Ketapang Aceh Besar - Sanur, Dimas; Thasrif Murhadi; Mahyuddin Mahyuddin (Politeknik Kampar, 2025)
The purpose of this study was to determine the influence of Store ATMOSPHERE, Word-of-Mouth Promotion, and Service Quality on the Decision to Use Services at AMAZON Barbershop in Ketapang, Aceh Besar, both simultaneously and partially. The population in this study was unknown, and the sample size was 96 respondents. Data were collected through questionnaires and documentation studies. Hypothesis testing using multiple linear regression analysis, F-test (simultaneous) and t-test (partial) was intended to determine the effect of the independent variables on the dependent variable at a 95% confidence level. The results showed that, through partial tests, the variables Store Atmosphere, Word-of-Mouth Promotion, and Service Quality influenced the decision to use services at Suasana Barbershop Ketapang, Aceh Besar. A simultaneous test also examined the variables Store Atmosphere, Word-of-Mouth Promotion, and Service Quality.